Impact of Organizational Culture and Work Ethic on Employee Performance with Commitment as a Mediating Factor Among Generation Z Employees - Anwar, Witania Putri; Wahyono, G. Budi; Imron, Moh.; Martaleni, Martaleni; Hadiyati, Ernani (Dinasti Research, 2025)
This study looks at how company culture and work ethic affect the performance of Generation Z employees, using employee engagement as a mediator. Data were obtained using an associative quantitative technique through an online survey of Generation Z employees (ages 18-28 with at least six months of service) and analyzed using PLS-SEM. The results show that company culture has a favorable and considerable impact on performance, both directly and indirectly through employee engagement. However, work ethic only has a major impact on performance when employee participation is fully mediated. One important result is that employee involvement does not directly boost Generation Z performance; rather, intrinsic motivation has a larger effect.